2020
DOI: 10.3389/fpsyg.2020.01467
|View full text |Cite
|
Sign up to set email alerts
|

“Art, Colors, and Emotions” Treatment (ACE-t): A Pilot Study on the Efficacy of an Art-Based Intervention for People With Alzheimer’s Disease

Abstract: Increasing evidence suggests that non-pharmacological therapies impact on neuropsychiatric symptoms and quality of life in people with Alzheimer’s disease. Among these, art-based interventions seem particularly suitable for elders’ rehabilitation as they act both on cognitive functions and quality of life. However, their benefits are not yet appropriately explored. The main aim of this quasi-experimental study was to test the feasibility and the likely efficacy of a novel multi-dimensional visual art intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 81 publications
(134 reference statements)
0
26
0
Order By: Relevance
“…Since holistic approaches to health care have gained more attention than in the past, there is a need for complementary or nonpharmacological approaches to better manage patients' health or symptoms 15,16,32,41. Moreover, some have argued that current pharmacological approaches can be used in combination with art making to reduce negative consequences (eg, drug interaction and side effects),30,31,42,43 or enhance health benefits from pharmacological approaches 4,7,18,31,44…”
Section: Resultsmentioning
confidence: 99%
“…Since holistic approaches to health care have gained more attention than in the past, there is a need for complementary or nonpharmacological approaches to better manage patients' health or symptoms 15,16,32,41. Moreover, some have argued that current pharmacological approaches can be used in combination with art making to reduce negative consequences (eg, drug interaction and side effects),30,31,42,43 or enhance health benefits from pharmacological approaches 4,7,18,31,44…”
Section: Resultsmentioning
confidence: 99%
“…This approach is based on evidence supporting the potential benefit of the modulation of neural activity in brain areas that are better preserved in the aging process, such as parietal areas ( Prakash et al, 2014 ). In particular, art-based stimulation resulted in a high effectiveness on different domains of functioning in AD, by acting on emotional channels and brain areas in which overactivation is observed in older adult age ( Bucks and Radford, 2004 ; Klein-Koerkamp et al, 2012 ; Savazzi et al, 2020 ). Finally, a predictive role of sex on the behavioral outcome was found as females were more likely to benefit from rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Careful examination of this disease stage showing the level of analytical impairment is important for best form of therapy. and it will evaluate the abilities and progresses are lost along the road [43][44][45][46][47][48].AD patients who are in the stage of mild /moderate will be better to compare advanced stage patients who are facing the difficulty in their daily life activities so they needed special care and motor and sensory dysfunctions are several required and more severe. Although analytical deterioration is proceeding, randomized restricted trails have found that using both Music and Art therapies benefitting the people with dementia and improving indicator assessment scores and improving and influencing the adults quality of life with the Alzheimer's disease [49].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the retention of motor and sensory capabilities in the cortex combined with delayed impairments in motor and visual functions allows for the creation of art, even if it is not high quality but rather abstract. The limbic system's relatively have good preservation facilitates like the expression of pleasant emotions and well-being [42,46,47,48,49,50].…”
Section: Therapy Of Artsmentioning
confidence: 99%